The Contribution of Fisheries Subsector Performance in Increasing Economic Growth in The Eastern Indonesia Region - Said Latuconsina; Darwati Susilastuti; Meirinaldi Meirinaldi; Widiyarini Widiyarini (PT. Publikasiku Academic Solution, 2023)
This research was conducted to determine the contribution of the performance of the fisheries subsector to economic growth in the Eastern Indonesia Region. Fishing is important for maintaining community identity, social cohesion and individual fishing status, and as the glue that binds communities together. Solutions to challenges in the marine and fisheries sector require a trend of insight and synergy at the regional level, such as IUU fishing, marine waste, fisheries trade barriers that are linked to tariffs. The Pooled Least Square Linear Regression method is used to analyze panel data using a quantitative approach. The sample data used is provincial data in WPPN RI 714, 715 and 718, which consists of 10 provinces cross-section data, 7 years of time series data. The result is that the performance of the fisheries subsector has a significant and positive influence on economic growth in the Eastern Indonesia Region. The magnitude of the influence of Fisheries Subsector Performance on Economic Growth is very strong and the increase is inelastic. The performance of the fisheries subsector can explain 89.92 percent of changes in economic growth. Measurable fishing is carried out to ensure the sustainability of fish resources is maintained and can provide fishermen's welfare, provide expansion and employment opportunities, increase added value and competitiveness due to fisheries, ensure business certainty, contribute to the world of business, and can increase economic growth.